Usefulness of Oral Fluid for Measurement of Methylone and Its Metabolites: Correlation with Plasma Drug Concentrations and the Effect of Oral Fluid pH - Sprega, Giorgia; Di Giorgi, Alessandro; Poyatos, Lourdes; Papaseit, Esther; Pérez-Mañá, Clara; Tini, Anastasio; Pichini, Simona; Busardò, Francesco Paolo; Lo Faro, Alfredo Fabrizio; Farré, Magí (Metabolites, 2023)
The aim of this study was to investigate methylone and its metabolites concentration in oral fluid following controlled increasing doses, focusing on the effect of oral fluid pH. Samples were obtained from a clinical trial where twelve healthy volunteers participated after ingestion of 50, 100, 150 and 200 mg of methylone. Concentration of methylone and its metabolites 4-hydroxy-3-methoxy-N-methylcathinone (HMMC) and 3,4-methylenedioxycathinone in oral fluid were measured using liquid chromatography–tandem mass spectrometry (LC–MS/MS). Pharmacokinetic parameters were estimated, and the oral fluid-to-plasma ratio (OF/P) at each time interval was calculated and correlated with the oral fluid pH using data from our previous study in plasma. Methylone was detected at all time intervals after each dose; MDC and HMMC were not detectable after the lowest dose. Oral fluid concentrations of methylone ranged between 88.3–503.8, 85.5–5002.3, 182.8–13,201.8 and 214.6–22,684.6 ng/mL following 50, 100, 150 and 200 mg doses, respectively, peaked between 1.5 and 2.0 h, and were followed by a progressive decrease. Oral fluid pH was demonstrated to be affected by methylone administration. Oral fluid is a valid alternative to plasma for methylone determination for clinical and toxicological studies, allowing for a simple, easy and non-invasive sample collection.